Interactive Instructional Materials for Grade 11 Students’ Reading Comprehension Remediation - Laputan, Alma (International Journal of Sustainability and Advanced Integrated Research, 2026)
This research assessed the effectiveness of the interactive instructional materials in improving the reading comprehension of the Grade 11 students at Lawaan National High School during the School Year 2024–2025 as the basis for the proposed enhanced instructional materials. It used a non-randomized one-group pretest-posttest quasi-experimental design. This study revealed that the Grade 11 students enrolled under the Academic Track had a good reading comprehension level in getting the main idea and in making inferences, and a fair reading comprehension level in summarizing events before they were exposed to the interactive instructional materials. However, the students had very good reading comprehension levels across all three variables after their exposure to the interactive instructional materials. Additionally, the data revealed that the difference between the pretest and posttest mean scores was statistically significant. Therefore, the interactive instructional materials were effective in enhancing the students’ reading comprehension. These materials are recommended for use during the reading remediation of Grade 11.
Keywords: Reading Comprehension, Interactive Instructional Materials, Quasi-Experimental Design, Philippines